2008
DOI: 10.1038/sj.ki.5002607
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcome in children with acute renal failure treated with peritoneal dialysis after surgery for congenital heart disease

Abstract: The present single-center cohort study was based on a clinical intensive care unit database containing data on 1128 consecutive children undergoing their first operation for congenital heart disease between 1993 and 2002 at Aarhus University Hospital, Skejby, Denmark. A total of 130 (11.5%) children developed postoperative acute renal failure (ARF) managed with peritoneal dialysis (PD). Logistic regression analysis was used to examine risk factors for complications related to PD and to compare mortality betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
71
1
8

Year Published

2009
2009
2014
2014

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(82 citation statements)
references
References 21 publications
1
71
1
8
Order By: Relevance
“…In a pediatric study, Perdensen et al (27) found a 11.5% incidence. Kuitunen et al (28) , evaluating adult patients, found a 19.3% rate, and these patients had less severe renal injury.…”
Section: Discussionmentioning
confidence: 99%
“…In a pediatric study, Perdensen et al (27) found a 11.5% incidence. Kuitunen et al (28) , evaluating adult patients, found a 19.3% rate, and these patients had less severe renal injury.…”
Section: Discussionmentioning
confidence: 99%
“…Even if the presence of AKI is usually associated with an increased rate of complications, longer hospital stay, and worse prognosis in this setting, the association between AKI and mortality must take into account the overall risk of death because of the underlying cardiac condition (19). In low-risk patients, the correlation between AKI and mortality was strong; in those with higher risk, the association was weaker, because death was attributable not only to AKI but also to other organ failure, especially cardiac failure (4). As in other series (19), we also found that longer bypass time was a predictive factor for a subsequent need for PD, although in our cohort, the severity of the cardiac disease did not correlate with the likelihood of RRT or mortality.…”
Section: Discussionmentioning
confidence: 99%
“…In this setting, PD or continuous venovenous hemodiafiltration can be offered to (3,4). In smaller children, PD may have some advantages because it obviates the need for a vascular catheter and is well tolerated in patients with hemodynamic instability (9).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations